The handbook of deviance - Goode, Erich (Hoboken : Wiley-Blackwell, 2015)
"The Handbook of Deviance is a definitive reference for professionals, researchers, and students that provides a comprehensive and engaging introduction to the sociology of deviance. Composed of over 30 essays written by an international array of scholars and meticulously edited by one of the best known authorities on the study of deviance Features chapters on cutting-edge topics, such as terrorism and environmental degradation as forms of deviance Each chapter includes a critical review of what is known about the topic, the current status of the topic, and insights about the future of the topic Covers recent theoretical innovations in the field, including the distinction between positivist and constructionist perspectives on deviance, and the incorporation of physical appearance as a form of deviance "--
"Cover recent theoretical innovation in the field, including the distinction between positive it and construction it perspective on deviance, and the incorporation of physical appearance a a form of deviance"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Deviant behavior; SOCIAL SCIENCE / Criminology; Deviant behavior; Electronic books